Transforming Enterprise Cloud Services - Chang, William Y.; Abu-Amara, Hosame; Sanford, Jessica Feng.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Transforming Enterprise Cloud Services addresses the fundamental ideology of Cloud Services and how enterprises in commercial, federal, and defense industries can transform their current information technology and management models to adopt this new method. It goes beyond the mere description of service frameworks in relation to cloud technologies and operations and provides practical path-forward solutions for identified challenges. For instance, as organizations transform their data and service models to compete in a new environment where data and services coexist with others in a public-held eco-system, enterprises have to face the challenge of data synthesis from a massive number of sources. One answer to this issue relies on a cross-organizational policy and technology coordination that can ensure that data will not be reproduced or manipulated by unauthorized entities. Transforming Enterprise Cloud Services explains how organizations can justify their current practices to take advantage of such collaboration synthesis securely, safely, reliably, and cost-effectively. Transforming Enterprise Cloud Services elucidates the service-oriented nature of Cloud Services and identifies issues and challenges from clients$1 (Band vendors$1 (Bperspectives. It also portrays how enterprise operators can successfully deploy their IT environment from both business and technical perspectives to enable massive scalability, high resilience, enforced security, and collaborative dynamics.s
to Enterprise Services and Cloud Resources1 -- Cloud Service Business Scenarios and Market Analysis1 -- Cloud Service Architecture and Related Standards3,2 -- Challenges of Enterprise Cloud Services1 -- Networked Service Management2 -- Cross-Domain Policy-Based Management1,3 -- Building and Configuring Enterprise Cloud Services3,2 -- Service Monitoring and Quality Assurance2 -- Security for Enterprise Cloud Services2 -- Enterprise Cloud Service Applications and Transformations1,2.
Keywords: Computer science; Computer Communication Networks; Information Systems; Telecommunication; Technology; Computer Science; Management of Computing and Information Systems; Technology Management; Communications Engineering, Networks; Computer Communication Networks